2011
DOI: 10.1124/jpet.110.172577
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and Challenges for Arterial Spin Labeling in Pharmacological Magnetic Resonance Imaging

Abstract: Pharmacological magnetic resonance imaging (phMRI) is increasingly being used in drug discovery and development to speed the translation from the laboratory to the clinic. The two primary methods in phMRI include blood-oxygen-level-dependent (BOLD) contrast and arterial spin-labeled (ASL) perfusion MRI. BOLD contrast has been widely applied in existing phMRI studies. However, because of the lack of absolute quantification and poor reproducibility over time scales longer than hours or across scanning sessions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 65 publications
4
84
0
Order By: Relevance
“…Another strength is the investigation of medication-induced alterations in CBF. Few fMRI studies effectively test medication-related CBF changes despite evidence of an interaction between basal physiologic and metabolic states and task-induced BOLD changes (Wang et al, 2011). The well-ascertained and clinically representative sample of individuals with methamphetamine use disorder also represents a strength, as it is often difficult to recruit individuals with severe drug addiction for clinical neuroscience research, yet these are precisely the individuals with which addiction science aims to help.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Another strength is the investigation of medication-induced alterations in CBF. Few fMRI studies effectively test medication-related CBF changes despite evidence of an interaction between basal physiologic and metabolic states and task-induced BOLD changes (Wang et al, 2011). The well-ascertained and clinically representative sample of individuals with methamphetamine use disorder also represents a strength, as it is often difficult to recruit individuals with severe drug addiction for clinical neuroscience research, yet these are precisely the individuals with which addiction science aims to help.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…It is important to note that CASL is a relatively new technique compared with PET, SPECT or even BOLD fMRI, 72 which might partly account for the lack of clinically relevant data in psychiatric samples 73 acquired with this specific method. Also, findings obtained under resting-state conditions do not necessarily imply either intact or deficient function of distinct brain regions when active cognitive, social or affective processing is required.…”
Section: Limitationsmentioning
confidence: 99%
“…6,8 While the exact dynamic relationship between neural function and CBF is not yet well known, considerable evidence suggests that imaging CBF alone offers a strong correlate of brain function. [9][10][11] While it has been shown that ASL provides an effective tool for rapid and safe estimation of blood flow in resting, task-related, and pharmacological functional MRI (FMRI) studies; 4,12,13 only a few studies have investigated how reliable these measures are and fewer still have looked at ways to improve this. For example, continuous ASL (CASL) techniques have been shown to be accurate and highly reproducible within 1-hour 14 and 7-week timeframes.…”
Section: Introductionmentioning
confidence: 99%